Implementasi Pemasaran Digital pada UMKM Pondok Vegetarian Top 68 dengan Menggunakan Media Sosial - Edy Yulianto Putra; Fiona Jocelyn (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
The world has now entered the era of the industrial revolution 4.0 because the internet has changed the rules of traditional marketing to digital. Quick and easy access to information on the Internet is a new way for MSMEs players to sell their products. One of them is by using social media marketing as a promotional medium, which has advantages in terms of being cheaper and more effective in marketing products sold by a business online. Social media plays an important role in today's MSMEs marketing strategy. One of the MSMEs here is Pondok Vegetarian Top 68 which was founded by Mrs. Anik in 2016. Pondok Vegetarian Top 68 is located at Perumahan Citra Kota Mas Blok B2 No. 10, Batam Center, Batam. Pondok Vegetarian Top 68 is an MSMEs that sells a variety of vegetarian foods. By making a business strategy, it aims to be able to make the best business strategy in today's digital era and to expand the reach of Pondok Vegetarian Top 68 consumers. This business strategy is to implement digital marketing using social media in the form of Instagram, WhatsApp Business, and Google Business. This project starts from September 2022 to December 2022. The results of the implementation of digital marketing through social media have been able to increase brand awareness which is certainly related to increased income for Pondok Vegetarian Top 68.